Evaluating effective swath width and droplet distribution of aerial spraying systems on M-18B and Thrush 510G airplanes - Zhang, Dongyan; Chen, Liping; Zhang, Ruirui; Hoffmann, Wesley Clint; Xu, Gang; Lan, Yubin; Wang, Xiu; Xu, Min (International Journal of Agricultural and Biological Engineering, 2015)
Aerial spraying plays an important role in promoting agricultural production and protecting the biological environment due to its flexibility, high effectiveness, and large operational area per unit of time. In order to evaluate the performance parameters of the spraying systems on two fixed wing airplanes M-18B and Thrush 510G, the effective swath width and uniformity of droplet deposition under headwind flight were tested while the planes operated at the altitudes of 5 m and 4 m. The results showed that although wind velocities varied from 0.9 m/s to 4.6 m/s, and the directions of the atomizer switched upward and downward in eight flights, the effective swath widths were kept approximately at 27 m and 15 m for the M-18B and Thrush 510G, respectively, and the latter was more stable. In addition, through analyzing the coefficients of variation (CVs) of droplet distribution, it was found that the CVs of the M-18B were 39.57%, 33.54%, 47.95%, and 59.04% at wind velocities of 0.9, 1.1, 1.4 and 4.6 m/s, respectively, gradually enhancing with the increasing of wind speed; the CVs of Thrush 510G were 79.12%, 46.19%, 14.90%, and 48.69% at wind velocities of 1.3, 2.3, 3.0 and 3.4 m/s, respectively, which displayed the irregularity maybe due to change of instantaneous wind direction. Moreover, in terms of the CVs and features of droplet distribution uniformity for both airplanes in the spray swath, choosing smaller CV (20%-45%) as the standard of estimation, it was found that the Thrush 510G had a better uniform droplet distribution than the M-18B. The results provide a research foundation for promoting the development of aerial spraying in China. Keywords: aerial spraying, effective swath width, droplet distribution, coefficients of variation, agricultural airplane DOI: 10.3965/j.ijabe.20150802.1493